Determination of Tannin Content in Matoa Plants (Pometia pinnata) Based on Variations in Leaf Age - Ulandari, Uci; Masriani, Masriani; Sasri, Risya; Ersando, Ersando (Universitas Pendidikan Mandalika, 2024)
The growth of the textile industry contributes significantly to environmental pollution from dye waste. The use of natural dyes from plants could be a solution to this problem, although they have weaknesses such as easy fading and less stable colors. Therefore, to improve color stability, a mordant is needed as a color fixative. Biomordants are mordants derived from plants that can be used as substitutes for metal mordants to bind dye to fabric fibers. Matoa leaves are one of the plants with the potential to be used as a biomordant because they contain tannin compounds. This study aims to determine the tannin content of methanol extracts of matoa leaf with various leaf age variations that can be used as a biomordant. The old and young matoa leaves were macerated with methanol for 3 days. The tannin content was determined using the Folin Ciocalteu method using a spectrophotometer Ultra Violet (UV) dual beam with positive control of tannic acid at a wavelength of 755.8 nm. The yield of methanol extract from old matoa leaves was 5.42% and from young matoa leaves was 8.58%. Phytochemical screening of methanol extract of old and young matoa leaves revealed the presence of secondary metabolite content of tannins, phenolics, flavonoids, saponins, triterpenoids, and alkaloids. The total tannin content of methanol extract from old matoa leaves was 0.37% ± 0.03, lower than that of young matoa leaves, which was 0.44% ± 0.06. Based on this research, it can be concluded that matoa leaves contain tannins and have the potential to be used as a biomordant.